Transformative Leadership of Wali Nagari Pakan Sinayan Banuhampu Agam Regency in Achieving The Achievement of Nagari Rancak in 2018 - Annisa Aulia Putri; Syamsu Rizaldi; Ria Ariany (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2021)
Nagari Pakan Sinayan has been led by H.S. Dt. Kayo Nan Kuniang for the past two periods. In the first period, Wali Nagari Pakan Sinayan won the Provincial Wali Nagari competency competition. Whereas for the second period, Wali Nagari Pakan Sinayan succeeded in bringing Nagari Pakan Sinayan to an achievement as Nagari Rancak in West Sumatera. This article aims to describe and analyze the leadership of Wali Nagari Pakan Sinayan in achieving achievements as Nagari Rancak. Problems are analyzed using the four components of transformative leadership by Robbins and Judge. The method used is qualitative with a descriptive analysis approach. The results showed that Wali Nagari Pakan Sinayan Banuhampu District Agam Regency has implemented a transformative leadership model. Wali Nagari Pakan Sinayan pays attention to the community and draws himself closer to sitting together with the community not only in official forums. Furthermore Wali Nagari Pakan Sinayan also implemented participatory planning to stimulate the community to issue ideas in development. Furthermore, Wali Nagari is a figure that motivates and gives influence to all nagari communities. Wali Nagari pays attention without distinguishing the jorong who supports him or not in the Nagari Election. Keywords: Transformational Leadership, Wali Nagari, Nagari Rancak